Missed foreign body inhalation for 15-years: Case report and Review of Literatures - hussen, waleed M. (Journal of the Faculty of Medicine Baghdad, 2021)
Background:Foreign body inhalation is a life threating event in children and it is common in our country ,which is  a daily practice of Thoracic .It  can lead to morbidity even mortality in the hands of untrained or not well- trained doctors.Aim:Is to report a case of missed foreign body inhaled 15-years back, which is uncommonly reported in the literatures and to compare it with other studies reporting similar cases.Methods:The details, presentation, clinical findings, radiological appearance and the successful removal by a rigid bronchoscope under general anesthesia will be presented.Results:The successful removal of this long standing impacted foreign body (plastic whistle) using the rigid bronchoscope and the eventful outcome of patient’s clinical symptoms is elucidated.Conclusion:Refractory respiratory symptoms of long duration without improvement justify the need for diagnostic bronchoscopy which will offers the best chance of cure in missed foreign body inhalation.